Is Inflation Domestic or Global? : Evidence from Emerging Markets - Bems, Rudolfs; Caselli, Francesca; Grigoli, Francesco; Gruss, Bertrand (Washington, D.C. : International Monetary Fund, 2018)
Following a period of disinflation during the 1990s and early 2000s, inflation in emerging markets has remained remarkably low and stable. Was this related to a global disinflation environment triggered by China's integration into world trade and the broader globalization in these economies, or to better domestic policies? In this paper, we review the inflation performance in a sample of 19 large emerging markets in the past couple of decades and quantify the impact of domestic and global factors in determining inflation. We document that the level, volatility, and persistence of inflation declined significantly, albeit not uniformly. Our results suggest that longer-term inflation expectations, linked to domestic factors, were the main determinant of inflation. External factors played a considerably smaller role. The results are a useful piece of evidence as emerging markets craft their monetary policies to navigate the future shift in global financial conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet